Testing a forgotten aspect of Akerlof's gift exchange hypothesis: Relational contracts with individual and uniform wages - Martin G. Kocher; Wolfgang J. Luhan; Matthias Sutter (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
Empirical work on Akerlof's theory of gift exchange in labor markets has concentrated on the fair wage-effort hypothesis. In fact, however, the theory also contains a social component that stipulates that homogenous agents that are employed for the same wage level will exert more effort, resulting in higher rents and higher market efficiency, than agents that receive different wages. We present the first test of this component, which we call the fair uniform-wage hypothesis. In our laboratory experiment, we establish the existence of a significant efficiency premium of uniform wages. However, it is not the consequence of a stronger level of reciprocity by agents, but of the retrenchment of sanctioning options on the side of principals with uniform wages. Hence, implementing limitations to contractual freedom can have efficiency-enhancing effects.
urn:nbn:de:bvb:19-epub-12816-6
Keywords: C72; C91; C92; D21; J31; J50; 330; gift exchange; multiple agents; uniform contracts; collective wage; experiment; Lohnbildung; Austauschtheorie (Soziologie); Unvollständiger Vertrag; Effizienzlohn; Test